Complete Specification of APIs and Protocols for the MAFTIA Middleware - Armstrong, J. (2009)
This document describes the complete specification of the APIs and Protocols for the MAFTIA Middleware. The architecture of the middleware subsystem has been described in a previous document, where the several modules and services were introduced: Activity Services; Communication Services; Network Abstraction; Trusted and Untrusted Components. The purpose of the present document is to make concrete the functionality of the middleware components, by defining their application programming interfaces, and describing the protocols implementing the above-mentioned functionality